PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP TINGKAT KELULUSAN SERTIFIKASI GURU DAN DAMPAKNYA PADA KINERJA GURU PADA SMA NEGERI DI BANGKINANG KOTA - Zulfahmi Zulfahmi; Abshor Marantika; Zulher Zulher (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine the effect of competence and training on the passing rate of teacher certification and its impact on teacher performance at SMA Negeri in Bangkinang Kota. The population in this study were all teachers of SMAN 1 Bangkinang Kota and teachers of SMAN 2 Bangkinang Kota which were known to be 112 teachers. In this study, the entire population was sampled, so the number of samples in this study amounted to 112 respondents, the sampling technique was called the saturated census technique. The types and sources of data used in this study are primary data and secondary data. Data collection techniques in this study used a questionnaire, research files and interviews and data analysis techniques used in this study used descriptive analysis, questionnaire feasibility test and structural equation analysis with data analysis using Structural Equation Modeling (SEM). The results showed that competence had an effect on the passing rate of teacher certification at SMA Negeri in Bangkinang Kota, training had an effect on the passing rate for teacher certification at SMA Negeri in Bangkinang Kota, competence had an effect on teacher performance at SMA Negeri in Bangkinang Kota, training had an effect on teacher performance in SMA Negeri in Bangkinang Kota and the passing rate of teacher certification have an effect on teacher performance at SMA Negeri in Bangkinang Kota.